Pathological role of methionine in the initiation and progression of biliary atresia - Jiachen, Zheng; Paul Kwong Hang, Tam; Kenneth Kak Yuen, Wong; Vincent Chi Hang, Lui (Frontiers in Pediatrics, 2023)
Methionine (Met) is an essential amino acid, and its excessive dietary intake and/or its metabolism disturbance could lead to accumulation/depletion of hepatic Met and some of the key intermediates of these pathways, which would interfere normal liver function and would be associated with liver diseases. Biliary atresia (BA) is a life-threatening disease characterized by inflammatory fibrosclerosing changes of the intrahepatic and extrahepatic biliary systems and is the primary cause of obstructive neonatal cholestasis with a rapid course of liver failure. However, its pathogenesis remains unknown. Previous studies reported elevated Met level in patients with obstructive cholestasis, suggesting a potential link between Met and BA. This paper reviews the Met metabolism in normal conditions and its dysregulation under abnormal conditions, the possible causes of hypermethioninemia, and its connection to BA pathogenesis: Abnormal hepatic level of Met could lead to a perturbation of redox homeostasis and mitochondrial functions of hepatocytes, enhancement of viral infectivity, and dysregulation of innate and adaptative immune cells in response to infection/damage of the liver contributing to the initiation/progression of BA.